Interventions to improve participation in health‐care decisions in non‐Western countries: A systematic review and narrative synthesis - Hankiz Dolan; Mu Li; Lyndal Trevena (Wiley, 2019)
Abstract Background Patients' participation in medical decision making is an important aspect of patient‐centred care. However, there is often uncertainty about its applicability and feasibility in non‐Western countries. Objective To provide an overview and assessment of interventions that aimed to improve patients' participation in decision making in non‐Western countries. Method Ovid Medline, Embase, Cochrane Central Register of Controlled Trials, CINAHL, Ovid MEDLINE(R) Epub Ahead of Print, In‐Process, Other Non‐Indexed Citations, without Revisions and Daily Update and Database of Abstracts of Reviews of Effects, were searched from respective inception to February 2018. Studies were included if they (a) were randomized controlled trials, before‐and‐after studies and interrupted time series studies; (b) were conducted in non‐Western countries; (c) aimed to improve patients' participation in dyadic decision making; and (d) reported outcomes relevant to patient participation in decision making. Studies were excluded if they included children, were about triadic decision making or solely focused on information provision without reporting outcomes related to patient participation. Narrative synthesis method was used for data analysis and presentation. Results A total of 17 studies, 6 RCTs and 11 non‐RCTs, were included across ten countries. Intervention strategies included patient and/or provider communication skills training, decision aids and a question prompt material. Whilst most of the studies reported increased patient participation, those interventions which had provider or patient training in communication skills were found to be more effective. Conclusion Interventions to improve patient participation, within the context of dyadic decision making, in non‐Western countries can be feasible and effective if communication skills training is provided for health‐care providers and/or patients.